Prenatal detection of D trisomy - Laurence, K. M. (1974)
The second instance of a prenatally diagnosed fetus of D trisomy is reported in a 45-year-old woman. The fetus had bilateral hare lip and cleft palate, arrhinencephaly, and numerous other malformations.